NICU Nurses' Suggestions for Improving End-of-Life Care Obstacles. Issue 1 (February 2019) - Beckstrand, Renea L.; Isaacson, Rebecca F.; Macintosh, Janelle L.B.; Luthy, Karlen E.; Eden, Lacey
Abstract: Background: Neonatal deaths (infants less than 28 days old) account for two thirds (66.7%) of all infant deaths with most occurring in an ICU setting. NICU nurses are frequently involved in end-of-life (EOL) care and face unique obstacles. Objective: The objective of this study was to obtain NICU nurses' suggestions for improving obstacles in EOL care in NICUs. Methods: Suggestions were obtained through mailed survey research in qualitative study design. Returned surveys yielded 121 nurse respondents who gave a total of 138 suggestions. Results: A total of 10 cohesive themes were identified: (1) environmental design issues, (2) improved communication between healthcare teams, (3) ending futile care earlier, (4) realistic and honest physician communications to families, (5) providing a "good death, " (6) improved nurse staffing, (7) need for EOL education, (8) earlier entry into hospice/palliative care, (9) availability of ancillary staff, and (10) allowing parents more time to prepare for death. Conclusions: Despite the variety of obstacles encountered in providing EOL care to dying infants and their families, NICU nurses can influence environmental factors, help improve communication, and use self-assessment tools to identify current EOL care practices.